Green Logistics Implementation In Malaysian Logistics Industry - Lew, Rose Ai Fen; Chew, Boon Cheong; Abdul Hamid, Mohd Syaiful Rizal (American Scientific Publishers, 2018)
As the world ecology is becoming worse due to globalization and industrialization with the rising temperature and sea levels, many global logistics companies are applying green logistics as it is both economy and environment sustainable. Smaller and local Malaysian logistics companies are also trying to implement green logistics but faced certain obstructions such as financial insufficient, limited access of know-how and so on. The main objective of this paper is to identify and examine the ways to implement green logistics. In this case study, a global logistics company which is DB Schenker Malaysia was chosen as the research location. Qualitative data were obtained through various literatures and through 30 semi-structured open-ended interviews using purposive sampling. Data were then analyzed using thematic analysis. This study found that there were five main ways to implement green logistics which are by using green packaging, green storage, green technology, green transportation and reverse logistics. Findings also indicated that there were gaps between the chosen global logistics company and various literatures findings in terms of the ways to implement green logistics. The five main ways of implementing green logistics mentioned in this research can be used as a guide and also as a motivator for going green to the Malaysian logistics industry. Future improvement can be done by identifying ways to implement green logistics in other industries such as food and beverage industry or semiconductor industry to increase validity.